2007
DOI: 10.1074/jbc.m702247200
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Segment S6 Determines Cation versus Anion Selectivity of TRPM2 and TRPM8

Abstract: TRPM2 and TRPM8, closely related members of the transient receptor potential (TRP) family, are cation channels activated by quite different mechanisms. Their transmembrane segments S5 and S6 are highly conserved. To identify common structures in S5 and S6 that govern interaction with the pore, we created a chimera in which the S5-pore-S6 region of TRPM8 was inserted into TRPM2, along with a lysine at each transition site. Currents through this chimera were induced by ADP-ribose (ADPR) in cooperation with Ca 2؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…It should be noted that this chimera differs from a previously characterized one that was anion-selective due to the single amino acid exchange I1045K (indicated in Fig. 1) (19). In whole-cell experiments with ADPR (0.05-0.6 mM) added to the pipette fluid or after extracellular stimulation with 10 mM hydrogen peroxide, this chimera displayed cation-selective currents with a linear I-V relation that were readily blocked in the inward direction by NMDG.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It should be noted that this chimera differs from a previously characterized one that was anion-selective due to the single amino acid exchange I1045K (indicated in Fig. 1) (19). In whole-cell experiments with ADPR (0.05-0.6 mM) added to the pipette fluid or after extracellular stimulation with 10 mM hydrogen peroxide, this chimera displayed cation-selective currents with a linear I-V relation that were readily blocked in the inward direction by NMDG.…”
Section: Resultsmentioning
confidence: 73%
“…The corresponding amino acid sequences of TRPM2 and TRPM8 are shown in single-letter code, and conserved residues are shown in boldface. The site within S6 where the exchange of a hydrophobic residue with a lysine reverses the charge selectivity of the pore in both TRPM2 and TRPM8 is marked with an asterisk (19). mean open time was 293 Ϯ 11 ms (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because the 563 position in the last transmembrane domain of TRPV5 is close to Asp 542 , it is likely that A563T substitution may affect the architecture of the pore and make it more accommodating for Ca 2ϩ ion permeation, although the lack of an accurate three-dimensional structure of TRPV5 precludes a precise prediction how this happens. It has been recently demonstrated that the substitution of a hydrophobic amino acid residue with a positively charged lysine in the last transmembrane domain of TRPM2 and TRPM8 converts the channels from cation selective to anion selective (20). This suggests that amino acid residues in the last transmembrane domain may participate in defining ion permeation properties directly or indirectly by affecting the conformation of the amino acid residues in the cation filter at the adjacent pore region.…”
Section: Discussionmentioning
confidence: 99%
“…TM4 and the TM4-TM5 linker in TRPM8 determines its sensitivity to voltage, temperature and menthol , while the distal part of TM6 determines cation versus anion selectivity, at least in TRPM2 and TRPM8 channels (Kuhn et al, 2007).…”
Section: Structurementioning
confidence: 99%